2021
DOI: 10.1093/jncics/pkab027
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Adolescent and Young Adult Cancer Trial Enrollment: NCORP Site Perspectives

Abstract: Background Although it is well documented that adolescents and young adults (AYAs) with cancer have low participation in cancer clinical trials (CCTs), the underlying reasons are not well understood. We utilized the NCI Community Oncology Research Program (NCORP) network to identify barriers and facilitators to AYA CCT enrollment, and strategies to improve enrollment at community-based and minority/underserved sites. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 31 publications
0
38
1
2
Order By: Relevance
“…Additionally, patient navigators and psychologists can be particularly helpful to AYAs who are primary caregivers and may be less compliant with cancer treatment or even refuse to participate in a CT 40 . A study from the National Cancer Institute Community Oncology Research Program identified an “AYA champion” who prioritizes opening of AYA CTs, involves AYAs in the CT process, and integrates pediatric and adult oncologists as main facilitator for AYA participation in CTs 7,27,32,41 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, patient navigators and psychologists can be particularly helpful to AYAs who are primary caregivers and may be less compliant with cancer treatment or even refuse to participate in a CT 40 . A study from the National Cancer Institute Community Oncology Research Program identified an “AYA champion” who prioritizes opening of AYA CTs, involves AYAs in the CT process, and integrates pediatric and adult oncologists as main facilitator for AYA participation in CTs 7,27,32,41 …”
Section: Discussionmentioning
confidence: 99%
“…Research Program identified an "AYA champion" who prioritizes opening of AYA CTs, involves AYAs in the CT process, and integrates pediatric and adult oncologists as main facilitator for AYA participation in CTs. 7,27,32,41 Finally, fertility concerns were described by several oncologists (but not AYAs) as a potential deterrent to CT enrollment, particularly among female AYAs. Until recently there were no standard guidelines for fertility preservation, an expensive procedure often not covered by health insurance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently conducted a multi-site, qualitative study to overcome the limitations of these previous studies, and identified barriers and facilitators to AYA CCT enrollment at 5 NCI Community Oncology Research Program (NCORP) sites. 16 The NCORP currently comprises 46 sites (32 community sites, 14 minority/underserved sites). Each NCORP site is a network of multiple community-based clinics, referred to as affiliate sites.…”
Section: Introductionmentioning
confidence: 99%